Synthesis and Mechanical Properties of Laminates Based on Phenolic Resins Modified with Sodium Lignosulfonate - Taverna, María Eugenia (2016)
The reduction of phenol and/or formaldehyde consumption during phenolic resin synthesis is of great technological and scientific interest because of its economic and environmental implications. In this work, the addition of sodium lignosulfonate as par-tial replacement of phenol in the phenolic resol base resins used for decorative laminates production is experimentally studied. The work involves: i) the characterization and reactivation of lignosulfonate, ii) the industrial synthesis of traditional and modified resoles by replacement of 10%w/w of phenol, iii) the industrial impregnation of Kraft-type papers with the produced resins, iv) the production of laminates at laboratory and industrial scale, and, v) the measurement of their final properties. Tensile, bending and impact strength were evaluated. Modified laminates exhibited mechanical properties statistically comparable with those of traditional laminates. Industrial tests were carried out at Centro S.A, San Francisco, Córdoba.